Analysis of Students' Physics Conceptual Understanding using Five-Tier Multiple Choice Questions: the Newton's Law of Motion Context - Vania Angelia Putri; Putri Dwi Sundari; Fatni Mufit; Wahyuni Satria Dewi (Jurnal Penelitian Pendidikan IPA, 2024)
Conceptual understanding is one of the physics learning objectives that can support students' thinking skills. Understanding of concepts in physics learning is very important for students, so that learning outcomes can be achieved maximally. This study aims to analyze the level of understanding of students' concepts on the topic of Newton's law of motion. This research is a descriptive research with quantitative approach. The research was at SMAN 4 Padang, SMAN 6 Padang, and SMAN 12 Padang West Sumatera. The total sample was 218 students. The five-tier multiple choice questions was used as a research instruments. Before the questions were used, the questions were tested first in different schools with the aim of knowing the validity, reliability, difficulty level, and distinguishing power of the items. After testing, 14 questions were obtained that could be used in this study. The results showed that 13.37% of students scienctific conception, 9.53% of almost scientific conception, 42.01% of students lack of confidence, 30.14% of students have misconceptions, 0.98% of students have no conception, and 3.96% of students have undefined. Based on these results, it can be concluded that students' conceptual understanding of Newton's law of motion material is still low.